Influência da medicação prẽ-anestésica com midazolam e clonidina no nível de hipnose após indução anestésica com propofol e alfentanil em crianças. Monitorização pelo índice bispectral - Ganem, Eliana Marisa [UNESP]; Módolo, Norma Sueli Pinheiro [UNESP]; Vianna, Pedro Thadeu Galvao [UNESP]; Castigilia, Yara Marcondes Machado [UNESP] (My University, 2002)
Background and Objectives - Premedication is an anesthetic adjuvant which decreases both perioperative anxiety and the need for high anesthetic concentrations, in addition to producing amnesia and contributing to hemodynamic stability. Midazolam and clonidine are among preanesthetic drugs indicated for children. This study aimed at evaluating whether preanesthetic midazolam or clonidine influences hypnosis in children induced with propofol and alfentanil. Methods - Participated in this study 30 patients aged 2 to 12 years, physical status ASA I, undergoing elective surgeries, who were divided into 3 groups: G1- without premedication, G2 - oral midazolam (0.5 mg.kg-1), and G3 - oral clonidine (4 pg.kg-1), both administered 60 minutes before anesthesia. All patients received alfentanil (30 μg. kg-1), propofol (3 mg.kg-1), and atracurium (0.5 mg, kg-1). BIS values were evaluated before anesthesia induction (M1) and after tracheal intubation (M2). Analysis of variance was the statistical method used for age, weight, and height, and profile analysis was used for BIS values, considering significant p < 0.05. Results - In comparing the same moment (M1 or M2) among the three groups there were no significant differences. When comparing the two moments of a same group, M1 values were higher than M2 values in all groups. Conclusions - Midazolam and clonidine premedication have not influenced hypnosis level of propofol and alfentanil in children.
Influence of midazolam and clonidine premedication on hypnosis level after anesthetic induction with propofol and alfentanil in children. Bispectral index monitoring
Keywords: Alfentanil, propofol; Bispectral index; Clonidine, midazolam; Hypnotics; Monitoring; Preanesthetic Medication